Justification of the design of an aerodynamic separator for cleaning sunflower seed mixture waste - Koshulko, V.; Kudriavtsev, I.; Кошулько, В. С.; Кудрявцев, І. М. (ЦНТУ, 2024)
The aim of the research is to substantiate the structural and technological scheme of an aerodynamic separator for cleaning waste from sunflower seed mixtures, ensuring the separation of elongated particles based on their specific weight and morphometric characteristics. This is achieved by modifying the formation of pseudo-fluidized layers and the sequence of applying the principles of pseudo-fluidized flow generation. A method for separating bulk mixtures in a two-stage environment has been proposed. It includes the gravitational feeding of particles, increasing vibro-inertial impact, pseudo-fluidized medium generation, and the removal of dense fractions. Метою досліджень є обґрунтування конструктивно-технологічної схеми аеродинамічного сепаратора для очищення відходів насіннєвої суміші соняшника, який забезпечує розділення подовжених часток за питомою вагою та морфометричними характеристиками. Це досягається шляхом зміни формування псевдорозріджених шарів і послідовності використання принципів генерації псевдорозрідженого текучого середовища.
Обґрунтування конструкції аеродинамічного сепаратора для очищення відходів насіннєвої суміші соняшника
Keywords: waste; sunflower; separation; cleaning; корм; пресування; стиснення; чисельне моделювання